Physicochemical properties and storage stability of ultrasound-mediated WPI-stabilized fish oil nanoemulsions. (December 2016) - Nejadmansouri, Maryam; Hosseini, Seyed Mohammad Hashem; Niakosari, Mehrdad; Yousefi, Gholam Hossein; Golmakani, Mohammad Taghi
Abstract: This work aimed to study the effects of whey protein isolate (WPI) to fish oil (FO) weight ratio (WR), pH and storage temperature on the physicochemical properties and storage stability of sonication-mediated WPI-stabilized fish oil nanoemulsions. 20-min sonication (200 W, amplitude 80, cycle 0.7) resulted in the formation of nanoemulsion with an average particle size of 84 nm. Increasing in WPI:FO WR and pH led to an increase in refractive index, viscosity and surface tension and a decrease in particle size and optical density. The equilibrium particle size was likely the consequence of protein concentration, aggregation of sonication-mediated depolymerized fractions as well as structural organization; which could result in more or less protein loading at the interface. The oxidation rate of WPI-stabilized nanoemulsions was less than that of corresponding emulsions having larger droplets maybe due to an increase in the antioxidant capacities of WPI fractions as a result of sonochemical reactions and development of protein layers of more thickness at the interface. The degradation of unsaturated fatty acids present in (nano)emulsions was influenced by storage temperature as determined by gas chromatography analysis. Morphological study performed by AFM confirmed the results obtained by laser diffraction technique. Graphical abstract: Highlights: An increase in refractive index and viscosity by increasing WPI:FO WR and pH. A decrease in particle size and absorbance by increasing WPI:FO WR and pH. Decreased oxidation rate of nanoemulsions as compared to emulsions. The emulsion viscosity was influenced by particle surface charge. Degradation of ω-3 essential fatty acids as a function of storage temperature.